Evaluación económica del régimen impositivo simplificado del Ecuador – rise - y su impacto tributarío - Malavé Galarza, Loren (2009)
The aim of this paper is a study on the impact of the RISE as a measure to regulate the informal economy by the Tax Administration, this work shows an analysis on informality in Ecuador, based with the latest changes in its methodology and concept. It will cover the main features of the RISE in our country as well as the impact of regimes in some Latin American countries. For the analysis of potential contributors (informal) will use cross - section data of the hand with a Binary Response Model with the aim of finding the profile of these taxpayers, we are going to realize that the results are similar to previous studies. Furthermore, we show if this regime filled the expectations of the Tax Administration this through the implementation of the goals established and a Cost – Benefit study.